Colourants on the wall paintings of a mediӕval fortress at the mount Sofeh in Isfahan, central Iran. (February 2020) - Holakooei, Parviz; Karimy, Amir-Hossein; Saeidi-Anaraki, Fariba; Vaccaro, Carmela; Sabatini, Francesca; Degano, Ilaria; Colombini, Maria Perla
Highlights: Madder red has been used as a historical colourant in Iran. Atacamite is a common green pigment in the Persian painting history. Raman spectroscopy is major diagnostic tool for the identification of ancient pigment. Local gypsum deposits have been used at the mount Sofeh in Isfahan, Iran. Abstract: Colourants on the twelfth century wall paintings excavated at the fortress located on the mount Sofeh in Isfahan, central Iran, were analysed using micro X-ray fluorescence (µ-XRF), micro Raman spectroscopy (µ-Raman) and high-performance liquid chromatography coupled to electrospray ionization quadropole time-of-flight (HPLC-ESI-Q-TOF). The results of the analyses showed that gypsum, atacamite, carbon black, orpiment and ultramarine blue were used as white, green, black, yellow and blue pigments, respectively. Moreover, three red colourants including red lead, red vermilion and madder red were identified in the wall paintings. Furthermore, possible sources for the colourants are discussed.